Preparation and Characterization of CdS Intercalated Montmorillonite for Potentiometric Sensor Fabrication - Udomphan, Kemawadee; Wongchaisuwat, Atchana; Meesuk, Ladda (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.24, 2021)
In this investigation, CdS intercalated montmorillonite (CdS-MMT) was prepared by an in situ solid-solid reaction between Cd-montmorillonite (Cd-MMT) and Na 2 S as 1:1 molar ratio. The intercalated material was characterized by using X-ray diffraction (XRD), Fourier Transform Infrared Spectrophotometry (FT-IR) and Field Emission Scanning Electron Microscopy with Energy X-ray Dispersive (FE-SEM-EDX). According to XRD and FT-IR results, the basal spacing of interlayer space was significantly increased and also the intensity of Si-O-Si vibration stretching at wavenumber 1,000 cm -1 was decreased after treated by ion exchange. FE-SEM showed that clay crystal has flake like shape, resemble pillar structure. EDX quantitative data exhibited atomic (%) of Cd and S to be 7.64 and 5.23 % respectively. The ratio of sulfur and cadmium (S/Cd) was found 0.68 which closed to 1:1 molar ratio. The use of CdS-intercalated montmorillonite for electrochemical sensor is proposed. Keywords : montmorillonite, intercalation compounds, potentiometric sensor, clay modified electrode